Chemical synthesis of guanosine diphosphate mannuronic acid (GDP-ManA) and its C-4-O-methyl and C-4-deoxy congeners. (10th October 2017) - Zhang, Qingju; Howell, P.Lynne; Overkleeft, Herman S.; Filippov, Dmitri V.; van der Marel, Gijsbert A.; Codée, Jeroen D.C.
Abstract: Described is the first synthesis of guanosine diphosphate mannuronic acid (GDP-ManA), the sugar donor used by algae and bacteria for the production of alginate, an anionic polysaccharide composed of β-d -mannuronic acid (ManA) and α-l -guluronic acid (GulA). Understanding the biosynthesis of these polyanionic polysaccharides on the molecular level, opens up avenues to use and modulate the biosynthesis machinery for biotechnological and therapeutic applications. The synthesis reported here delivers multi-milligram amounts of the GDP-ManA donor that can be used to study the polymerase (Alg8 in Pseudomonas aeruginosa ) that generates the poly-ManA chain. Also reported is the assembly of two close analogues of GDP-ManA: the first bears a C-4-O-methyl group, while the second has been deoxygenated at this position. Both molecules may be used as "chain stoppers" in future enzymatic ManA polymerisation reactions. The crucial pyrophosphate linkage of the GDP-mannuronic acids has been constructed by the phosphorylation of the appropriate ManA-1-phosphates with a guanosine phosphoramidite. Graphical abstract: Highlights: First chemical synthesis of Guanosine Diphosphate Mannuronic Acid. Chemical synthesis of C-4 modified GDP-ManA analogues. Pyrophosphate formation with phosphoramidite.